Analysis of Needs for Facilities and Infrastructure in the Physics Learning Media Laboratory at Muhammadiyah University Prof. Dr HAMKA - Fahira, Adinda Permata; Ermawati, Imas Ratna; Sugianto (Universitas Mandiri, 2024)
Laboratories in lectures are very important in equipping students to study physics concepts, physics learning media laboratories can be a means for students to learn more about interesting and interactive physics learning tools and media. In this research, researchers used a quantitative survey research method with data collection techniques used in the form of non-tests and the tools used were questionnaires. Based on the results of the analysis using winsteps software, I8 (item number 8), I23 (item number 23) and I15 (item number 15) are not suitable because they do not meet the existing criteria, namely Outfit ZSTD (Z-Standardized Values), when viewed from Outfit MNSQ (Mean Square Values) and PT Measure-CORR (Point Measure Correlation) all items can be said to be valid. Based on the data obtained, it can be said that respondents answered according to the criteria. Therefore, the laboratory facilities and infrastructure of Prof. Dr. Hamka Muhammadiyah University meet the criteria. Cronbach's alpha with a score of 0.79 shows good results so that the item is said to be reliable. The person reliability value displays a score of 0.78 and the item reliability value displays a score of 0.88. The value of person reliability shows that the consistency of answers from students is